Стратегічні запаси нафти, нафтопродуктів і природного газу у країнах Центральної Європи – їхня загальна характеристика та досвід функціонування - Дудкін, О. М.; Dudkin, O. (Видавництво Львівської політехніки, 2017)
У статті розглянуто досвід створення та функціонування стратегічних резервів нафти, нафтопродуктів і природного газу як ключового елементу забезпечення енергетичної безпеки національної економіки на випадок кризи постачання країн Центральної Європи – Угорщини, Чехії, Словаччини та Польщі. Зокрема, розглянуто моделі таких резервів, особливості їхнього функціонування. Сформовано власний погляд щодо необхідності використання досвіду країн Центральної Європи при створенні системи стратегічних резервів нафти, нафтопродуктів та природного газу в Україні.

The article deals with the experience of creating strategic reserves (stockpiles) of oil, petroleum products and natural gas as a key instrument in ensuring energy security in the event of a supply crisis and a factor to remain economy functioning in Central European States – Czech Republic, Slovakia, Poland and Hungary. All these states have common feature – they are highly dependent on import of oil and gas, most of them have approximately 100% import dependency almost from one source – Russian Federation. As result, they are extremely vulnerable to energy crisis, which may be provoked by political reasons. On the level of European Union and International Energy Agency, emergency response system has next four pillar elements: stockpiling system, demand restraint measures, fuel switching (temporarily replacing with other energy sources) and surge production. In particular, were characterized models of functioning of such reserves (Public and Industry and their sub-models), regulatory framework and system of demand restraint measures. However, all above-mentioned states have common system of emergency response and demand restraint measures, put in place a National Energy Strategy Organisation as central body for coordination emergency policy. But, each of them have their own experience regarding creating of stockpiles system counting peculiarities of their regional development, oil market structure, national policy choices etc. For example, Slovakia recently had changed its model of oil reserves, Hungary was first in the region and in EU to introduce gas-stockpiling system with necessary legislative amendments, Poland has strengthened role of state in its stockpiling system. Regarding demand restraint measures, which aim rapidly to reduce consumption in a crisis, it necessary to underline that Central European States mostly have implemented them and prescribed them in their national regulatory documents. The degree, to which measures could be applied can range from light handed (such as public information campaign) to more medium and heavy-handed compulsory measures (driving restrictions and fuel rationing). Hungary has implemented demand restraint measures from 1979, what can be counted as the oldest developed system of demand restraint measures in Central Europe. Other measures for supply crisis reaction and management such as fuel-switching and surge of oil and gas production have no significant potential in above mentioned states. Given own opinion about usefulness of researched states experience for Ukraine as it has according to its obligations within Energy Community and according to Ukraine – EU Association Agreement to create its own stockpiling system until 2022.
Strategic stocks of oil, petroleum products and natural gas in central European states – general characteristics and experience of functioning
Keywords: стратегічні резерви нафти; нафтопродуктів та природного газу; моделі функціонування резервів; енергетична криза; енергетична політика; energy crisis; energy policy; strategic reserves (stockpiles) of oil; petroleum products and natural gas; models of functioning of stocks – Industry Public State Agency; demand restraint measures; production surge; fuel-switching; 338.2